KUALITAS PAPAN PARTIKEL DARI AMPAS BATANG SAGU (Metroxylon spp) DENGAN PEREKAT ALAMI ASAM SITRAT : SIFAT FISIK, MEKANIK DAN KEAWETAN TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Wesly, Yonatan; Dirhamsyah, M; Setyawati, Dina; Nurhaida, . (Universitas Tanjungpura, 2019)
AbstractThis study is intended to focus on the concentration of natual citric acid and density including physical and mechanical properties and durability of particleboards towards C. curvignathus Holmgren. This research is lifted because research on the use of citric acid as an adhesive is relatively limited.The researchâ€™s material was taken from waste dreg of Sago and citric acid. The research was carried out in wood workshops, wood processing technology laboratories and forest product technology laboratories, Tanjungpura University Forestry Faculty along with laboratories PT Duta Pertiwi Nusantara. The factors which was used in this study was the concentration of 20% - 30% with a density of 0,6 g/cm3 and 0,7 g/cm3 , based on the weight of the airborne particle, the temperature of pressurization used 180ÂºC with pressures of 25 kg/cm2. Physical and mechanical properties were tested based on JIS A 5908-2003 type 8. Testing of soil termites was carried out by calculating the value of weight reduction and mortality of termiste after 21 days. In this study, The optimum conditions were particle board density 0,7 g/cm3 and concentration 20%, with qualities that can fulfill several standards of JIS A 5908-2003 type 8, with a density of 0,7 g/cm3 consentrations 30%, resulting in termite mortality values of 100% and loss16,92% of weight.Keywords : Citric acid, concentration, density, termite, sago.